Character Education: Its Implementation at Islamic Boarding School - Fauzi, Imam -; Syafe’i, Imam; Amiruddin, Amiruddin (Journal of Advanced Islamic Educational Management, 2022)
Character education aims to instill good moral principles in students so they can use them in their everyday lives. One educational system that aims to produce noble souls is pesantren. Character education in pesantren can make a significant contribution to students' moral development. To achieve the best results for the character development of the students, character education in the pesantren is carried out using a multidisciplinary approach. Students' moral development can benefit greatly from character education in the classroom. Finding out how character education is applied at Pondok Pesantren Miftahul Falah Mataram Baru in East Lampung, Indonesia, is the aim of this study. Teachers, administrators, students, and the neighborhood surrounding the pesantren served as the trusted informants who controlled the information and provided the necessary data. Data collection was done through interviews, observation, and documentation. Data analysis was carried out in several stages, namely, data collection, data reduction, and drawing conclusions. The results of this study indicate that the implementation of character education at Miftahul Falah Islamic Boarding School is carried out using several methods, namely exemplary, habituation, and giving advice or direction.